Determinación del espectro de reflectancia difusa del ecosistema herbazal de páramo en la subcuenca del Río Chambo provincia de Chimborazo - Iván Danilo, Zavala Loza (2018)
The objective of this work was determine the diffuse reflectance spectrum (DRS) of Paramo Herbazal Ecosystem (PHE) in Chambo river Sub-basin, province of Chimborazo. An exploratory map was developed with the normalized difference vegetation index (NDVI) values of the study area, using Landsat 8 images metadata and categorization of NDVI values proposed by NASA. We recorded in field, the “experimental” and “calculated” diffuse reflectance spectrum from the strata previously identified. We calculate the NDVI values, using the spectrum “calculated” and “experimental”, of each strata and the Paramo Herbazal Ecosystem, and framing these values with the coverage categories of the paramo according to the NDVI value. Thus, the PHE “spectral signature” from Chambo River Sub-basin was obtained, as well as its main coverage. Three Paramo Herbazal Ecosystem strata were identified: the EHP-3 characterized by the dominance of the Calamagrostis Intermedia (51%) and Calamagrostis Effusa (49%), the EHP-4 where the dominant specie is Calamagrostis Effusa (72%) and in the EHP-5 dominated by Cortaderia Bifida (71%). This study shows that the “experimental” and “calculated” DRS coverage from EHP, combined with satellite images metadata is a methodological alternative that can be used to evaluate the vegetation cover and monitor the environment in the Paramo Herbazal Ecosystem. Consequently, this study can be applied in other areas as an effective tool for the monitoring of vegetation changes in the Paramo ecosystems.